PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) PADA PESERTA DIDIK KELAS VI B UPT SPF SD INPRES BONTOMANAI KOTA MAKASSAR - Harliwan; Fatima Gita Mutmaina; Munawwarah Thalib (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine whether there is an increase in student learning outcomes in the Pancasila Education Subject through the Teaching at the Right Level (TaRL) approach in class VI B UPT SPF SDI Bontomanai. This research uses the Classroom Action Research (PTK) method which is carried out over two cycles with stages of planning, implementation, observation and reflection. The instruments used are observation, learning results tests and documentation. The research subjects were class VI B UPT SPF SDI Bontomanai with 27 students. The indicator of success in this research is an increase in student learning outcomes in each cycle. The results of this research show that the percentage of completeness of students' learning outcomes in pre-cycle learning was 44% with an average value of 58. There was an increase in learning cycle I with the percentage value of completeness of learning outcomes reaching 67% and continued to increase in learning cycle II with the percentage of completeness of learning outcomes learning was 85% with an average score of 77. The percentage difference in student learning outcomes from pre-cycle learning to cycle I was 23%, and from cycle I to cycle II was 18%. Based on these results, it can be concluded that student learning outcomes in Pancasila Education subjects can be improved through the application of the Teaching at the right Level (TaRL) approach.